Tracking the pre-service teachers' development of communicative skills and their beliefs towards communicative approach - Yıldıray Kurnaz; Ali Şükrü Özbay (Journal of Pedagogical Research, 2020)
Concerns about the purpose of developing communicative skills in English teaching and approaches to overcome these concerns have always had an important place in language teaching. In this context, besides the fact that teachers' roles are important, their beliefs about the approach have a profound influence on their professional achievement. In this regard, the aim of the present study was to determine Turkish English as a Foreign Language (EFL) student teachers' beliefs about developing their communicative skills with the communicative approach in Turkish context. The data obtained through Pre-Service Teacher Beliefs Questionnaire, in which 445 participants took part, and focus group interviews with 28 participants at several times and places were analysed by quantitative and qualitative data analysis methods respectively. As a result of the analysis, it was found that EFL student teachers generally had positive attitudes towards improving communicative skills of their prospective students with communicative approach; however, it was difficult for this approach to work properly in Turkey and in Turkish education system due to various reasons. In addition, it was found that EFL student teachers' self- efficacy beliefs were correlated with their attitudes towards the approach, and that many sub-factors such as second language proficiency also had an influence on the attitudes. Lastly, these findings were found to be significantly different according to the departments (ELL, ELT) rather than age and gender.